From the Blood-Brain Barrier to Childhood Development: A Case of Acute-Onset Psychosis and Cognitive Impairment Attributed to Systemic Lupus Erythematosus in an Adolescent Female. Issue 1 (January 2022) - Johnson, Matthew C.; Sathappan, Aakash; Hanly, John G.; Ross, Gail S.; Hauptman, Aaron J.; Stone, William S.; Simon, Kevin M.
Abstract : Learning objectives: After participating in this CME activity, the clinician will be better able to: Interpret classifications of neuropsychiatric systemic lupus erythematosus (NPSLE). Identify determining factors of neuropsychiatric events. Analyze current evidence regarding disease pathways for NPSLE.